Tan Malaka, Gerakan Kiri, Dan Revolusi Indonesia - Setiawan, Hersri (Yayasan Obor Indonesia; KITLV-Jakarta, 2008)
Judul Asli : Verguisd en vergeten; Tan Malaka, de linkse beweging en de Indonesische Revolutie, 1945-1949